2007
DOI: 10.1128/iai.02083-05
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Immunostimulating Lipoprotein Existing in the Natural Lipoteichoic Acid Fraction

Abstract: Lipoteichoic acid (LTA) is a cell surface glycoconjugate of gram-positive bacteria and is reported to activate the innate immune system. We previously reported that purified LTA obtained from Enterococcus hirae has no immunostimulating activity, but a subfraction (Eh-AF) in an LTA fraction possesses activity. In this study, we established a mouse monoclonal antibody neutralizing the activity of Eh-AF and investigated its inhibitory effects. Monoclonal antibody (MAbEh1) was established by the immunization of BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 40 publications
1
37
1
Order By: Relevance
“…Our data are in support of those of Hashimoto et al (15)(16)(17) who reported that contaminating BLPs carry the immunostimulatory activity commonly assigned to LTA from S. aureus. Thus, in contrast to LTA, GBS BLPs qualify as highly potent bacterial toxins.…”
Section: Detection Of Blps With [supporting
confidence: 82%
See 1 more Smart Citation
“…Our data are in support of those of Hashimoto et al (15)(16)(17) who reported that contaminating BLPs carry the immunostimulatory activity commonly assigned to LTA from S. aureus. Thus, in contrast to LTA, GBS BLPs qualify as highly potent bacterial toxins.…”
Section: Detection Of Blps With [supporting
confidence: 82%
“…However, the LTA response was amplified only by muramyl dipeptides (MDP), the minimal PGN fragments that interact with the intracellular NOD receptors, and not by macromolecular PGN (5,13,14). In disagreement with this model, however, recent work from Hashimoto and colleagues (15)(16)(17) challenged LTA from S. aureus as a TLR2 agonist altogether. Hence, we were left with the puzzle of whether LTA might act in concert with other GBS substructures (e.g., MDP) in vitro and in vivo or whether molecules from GBS other than LTA were more potent stimulants of TLR2.…”
Section: G Roup B Streptococcus (Gbs)mentioning
confidence: 81%
“…The latter authors demonstrated a 100-fold decreased immunostimulatory capacity of LTA preparations derived from a Dlgt deletion mutant S. aureus lacking palmitate-labeled lipoproteins compared with LTA from the respective wild-type (wt-LTA) strain. From this finding and from other observations, they concluded contaminating lipoproteins in the LTA preparations to be responsible for LTA-mediated immune activation (24)(25)(26). Contrary to the latter investigators (27), we found that LTA of a mutant S. aureus strain lacking lipoproteins (Dlgt-LTA) and wt-LTA were equipotent in inducing cytokine release from human whole blood.…”
contrasting
confidence: 54%
“…Despite strong evidence for a major role of LTA in the immune activation by Gram-positive bacteria (21)(22)(23), recent reports suggested that not LTA but lipoproteins are dominant immunobiologically active structures of S. aureus (24,25). The latter authors demonstrated a 100-fold decreased immunostimulatory capacity of LTA preparations derived from a Dlgt deletion mutant S. aureus lacking palmitate-labeled lipoproteins compared with LTA from the respective wild-type (wt-LTA) strain.…”
mentioning
confidence: 93%
“…Bacterial lipoproteins are anchored to bacterial membrane through three lipid chains covalently attached to the conserved N-terminal cysteine (37). Lipoteichoic acids are amphipathic molecules found in the membrane of Gram positive bacteria and induce strong proinflammatory signals in macrophages (38)(39)(40).…”
Section: Application To Tlr1 and 2 Crystallizationmentioning
confidence: 99%